2013
DOI: 10.1353/pla.2013.0020
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of the Student Population at an Urban University: How Do They Use a Joint Library?

Abstract: The King Library in San José, California, is a unique combination of academic and public library. It serves the diverse populations of the City of San José and San José State University (SJSU). This article provides analysis of data collected in a study on the concept of “library as place” and SJSU students’ sense of belonging toward the King Library building. This study involved a mixed quantitative-qualitative research approach. In total, 744 students were surveyed. The results show that SJSU students use th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The student survey consisted of two parts: a demographic questionnaire and multiple-choice questions on information literacy mastery and concepts. The demographic part of the student survey employed questions from one of the author's previous publications (Molteni, 2008 andMolteni, Goldman &Oulc'hen, 2013 …”
Section: Methodsmentioning
confidence: 99%
“…The student survey consisted of two parts: a demographic questionnaire and multiple-choice questions on information literacy mastery and concepts. The demographic part of the student survey employed questions from one of the author's previous publications (Molteni, 2008 andMolteni, Goldman &Oulc'hen, 2013 …”
Section: Methodsmentioning
confidence: 99%
“…17 Indeed, a number of studies have shown that many nonacademic activities such as eating, socializing, and sleeping also occur in the college library (see, for example, Cunningham and Tabur, 18 Gayton, 19 Lanclos, 20 Mizrachi, 21 and Suarez). 22 The challenges of competing uses for campus spaces, particularly the library, are greater for commuter students. Molteni, Goldman, and Oulc'hen found that students "seek to integrate their student and personal lives" in part because they lacked spaces on campus to keep them separate.…”
mentioning
confidence: 99%
“…Student commuting behavior reported to Clark (2005) corresponds well with the wide variety of passenger behaviors Lopatovksa et al (2011) observed on New York City subway cars and buses: reading and writing, though also listening to music and playing games. Molteni, Goldman, and Oulc'hen (2013) examine student use of King Library in San José, California that serves both the City of San José and San José State University (SJSU), a predominantly commuter institution. Results of their survey allow them to compare commute times with frequency of library use, and reveal that students "with shorter commutes spend more time in the library" (p. 247).…”
Section: Literature Reviewmentioning
confidence: 99%